Examining the Relationship between Work Stressors and Auditors’ Job Performance - Ali, Norlela Mohd; Ghani, Erlane K (International Journal of Management and Sustainability, 2022)
Workplace stress is a common problem in all types of occupations, and from the highest to the lowest levels of management. Auditors are not an exception to stress, particularly for those working in audit firms. To mitigate the auditors’ stress level, it is crucial for the management to identify work stressors on their job performance. This study aims to examine the relationship between work stressors and auditors’ job performance. Specifically, this study chose five potential work stressors namely, role ambiguity, work overload, time pressure, work/family conflict and salary and compensation. Using a questionnaire-based survey of 102 auditors, this study shows that role ambiguity and salary and compensation have a significant relationship with auditors’ job performance. On the other hand, this study shows that work overload, work/family conflict, and time pressure do not have a significant relationship with auditors’ job performance. The findings in this study provide an understanding for management of the work stressors that could affect the auditors’ job performance. Understanding this would assist the auditors to manage their stress properly, which could positively improve their performance.